Planning Internalization of Moderate Islamic Education - Ali Imran Sinaga; Ruwaidah Ruwaidah; Syamsu Nahar (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this research is to investigate the concept program of moderate Islamic education at Yayasan Nur Ibrahimy, the integrated schools of SMK Madani and SMA Muhammadiyah 10 Rantauprapat, including the steps, obstacles, support, and efforts involved. This research utilized a qualitative method and was conducted at Senior High School Nur Ibrahimy, the integrated school of SMK Madani, and SMA Muhammadiyah 10 Rantauprapat. The data collection techniques included interviews, field research, and documentation studies. The rolling technique and data analysis involved data reduction, analysis of available data, and conclusion. The research was conducted from May 21, 2023, to February 21, 2024. The research findings at SMK Madani identified four concepts: employing future life skills to combat violence or learning through the principles of Ahlu Sunnah Wal Jama'ah An-Nahdiyin. At MAS Nur Ibrahimy, the concepts included Islamic brotherhood (ukhuwáh Islámiyah), national brotherhood (ukhuwáh wathániyah), and human brotherhood (ukhuwáh Insániyah). SMA Muhammadiyah 10 focused on two concepts: Islamic education (al-Islam) and Muhammadiyah principles (Kemuhammadiyahan).